LEAD ‐ Leadership effectiveness, motivation, and culture in Africa: Lessons from Egypt, Ghana, Kenya, Nigeria, and Uganda. (December 2014) - Senaji, Thomas Anyanje; Metwally, Elham; Sejjaaka, Samuel; Puplampu, Bill Buenar; Michaud, James; Adedoyin‐Rasaq, Hassan
Abstract This exploratory study considers an African perspective on leadership behaviour and motivation in Ghana, Egypt, Kenya, Nigeria, and Uganda using the Delphi Technique with a small sample of corporate, community, and religious leaders. Focus group sessions with working people (nonleaders) then followed. The findings indicate that vision, commitment, honesty, goal‐orientation, and humour were descriptors of effective leadership. Further, it was found that the quest for justice, extrinsic benefits, and service to community motivated leaders, while extrinsic rewards and the need to achieve motivated followers. This research contributes to understanding leadership effectiveness and motivation from an African context and informs both scholarship and practice in these areas. Copyright © 2014 ASAC. Published by John Wiley & Sons, Ltd.